Crisis Scenarios for Risk Mitigation of Grey Rhino Paradigm Incidence on Value Added Continuity in Organizations - Burianova, Olga; Urbanek, J. F. (European Journal of Applied Sciences, 2024)
Grey Rhino (GR) paradigm represents strategic global threats. It is a metaphor for perils, threats, and risks, which are neglected for extent and for high probability of incidence. This paper investigates the relationships of GR case objective entities in environment of Value Added (VA) organization production continuity by the assessment of risk mitigation. The VA is economic operations quantity. It results from productivity controlling changes in economic processes. The VA affects to the calculations of the Value Added Tax in economic activities. An indicator of business continuity of organization processes is a ’from Operations’ Value Added (O’VA), which is essential informative parameter in our simulations. GR event impact is simulated by its hexagonal corner - an EDGE (the Expectable Disruptive Gradual Event). A Business Continuity Management (BCM) can face business continuity disturbances. Simulation indicator for risk of slip continuity organization is a RiSCO. It has great influence on relationships among the many by crisis injured entities. Higher RiSCO can injury a social – corporate responsibility. Against of the GR impact is necessary to create preventive measures in recent global economic crisis. They all are entities for our crisis simulation scenarios via DYVELOP (Dynamic Vector Logistics of the Processes).